Motorcycle handling and chassis design : the art and science. - Foale, Tony, ....- (Alicante : Tony Foale Designs, 2003)
The original book was first published in 1984 and very quickly became considered as the standard reference text. It was reprinted many times, lastly in 1998 but then quickly sold out. A German translation also became available in 1988. Written at a level to be comprehensible to the average reader it was also sufficiently detailed to be of interest to race technicians, students and engineers. The new book, published in 2002, introduces a wealth of additional material. It has more than five times the text content of the original and more than triple the number of illustrations and photographs. 510 information packed pages.
Keywords: Motorrijwielchassis